Experimental studies for general chemistry : a first-year laboratory manual including quantitative analysis for a first-year chemistry course - 214728 Nicol, Malcolm F.; Russell, Arlene A.; Siebert, Eleanor Dantzler (San Francisco : Holden-Day, 1973)
42